Comparing screening tools for subitising abilities in 5–6-year-olds : identifying early numeracy challenges - Holmqvist, Mona ; 0000-0002-8734-1224; Tutunjian, Damon; Wästerlid, Catarina ; 0000-0003-1299-1318 (Research in Mathematics Education, 2026)
The present study evaluates two different screening tools–the Ability to Quickly See Quantities (AQSQ) test and the Number Sense Test (NST) targeting subitising and part-whole relationships, respectively–to examine their potential to indicate early numeracy challenges. Seventy-four kindergarten students participated, and their performances on the two tests were analyzed using correlational analyses of measures derived from signal detection theory and qualitative comparisons. The results showed a moderate correlation between AQSQ and NST scores, indicating an overlap in measuring subitising. Both tests showed overlap in identifying students with lower scores, suggesting potential for early screening use, with a 64% overlap between the lowest quartiles of the two tests. The AQSQ may be a more practical single-choice option for resource-limited classrooms. Further research is needed to clarify the underlying similarities and differences in the constructs measured by the two tests and how they may contribute to understanding early numeracy development.
Publisher Copyright: © 2026 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Assessment; preschool class; subitising